Challenging childhood, challenging children: Children's rights and sexting. (September 2013) - Simpson, Brian
Concern with children's online safety dominated the early days of the internet, fuelled by a fear of online predators able to utilise online technologies to manipulate their identities and groom children. Such adults strike at long held notions of childhood innocence and often commit serious offences as a result. However, a possibly unforeseen consequence of new online technologies has been the apparent capacity they afford to children themselves to reconstruct the meaning of childhood and family relationships, especially in the age of mobile (and hence less capable of parental supervision) technology. A recent example of this is the phenomenon of 'sexting', which appears to be caught between debates on the sexual rights of children and the role of the state in protecting children from themselves. What I wish to explore, however, is whether such constructions of the debate are themselves static and belong to an older age. Instead, is it possible that online technologies are altering the dynamics of relationships which created romantic notions of childhood innocence in the past, and which now enable children to actively participate in the formation of their own identity? In other words, have new online technologies enabled the creation of new identities of childhood which challenge the order of childhood? If so, does this mean that regulations based on older notions of childhood are doomed to fail, or alternatively lead to such injustices in the eyes of young people that the law's legitimacy will be open to question?